2018
DOI: 10.1002/ece3.4448
|View full text |Cite
|
Sign up to set email alerts
|

Functional Redundancy in bird community decreases with riparian forest width reduction

Abstract: Riparian ecosystems are suffering anthropogenic threats that reduce biodiversity and undermine ecosystem services. However, there is a great deal of uncertainty about the way species composition of assemblages is related to ecosystem function, especially in a landscape fragmentation context.Here, we assess the impact of habitat loss and disturbance on Functional Diversity (FD) components Functional Redundancy (FRed), Functional Evenness (FEve), and Functional Richness (FRic) of riparian forest bird assemblages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 94 publications
1
6
0
Order By: Relevance
“…Insectivorous and omnivorous birds prevailed, as has been reported several times for urban areas (Chace and Walsh 2006;MacGregor-Fors 2008;Ortega-Álvarez and MacGregor-Fors 2011;Domínguez-López and Ortega-Álvarez 2014;Pena et al, 2017;Barbosa et al 2020). On the other hand, the present results agree with other studies developed in forested areas regarding the predominance of species with functional traits with some dependence on forest resources, such as mixed and understory foraging stratum and intermediate forest-dependence (e.g., riparian, Domínguez-López and Ortega-Álvarez 2014;Batisteli et al 2018;Maure et al 2018). The urban greenspaces studied here are forested (Online Resource 1a), which favors forestdwelling species that require specific resources in these urban landscapes.…”
Section: Discussionsupporting
confidence: 91%
“…Insectivorous and omnivorous birds prevailed, as has been reported several times for urban areas (Chace and Walsh 2006;MacGregor-Fors 2008;Ortega-Álvarez and MacGregor-Fors 2011;Domínguez-López and Ortega-Álvarez 2014;Pena et al, 2017;Barbosa et al 2020). On the other hand, the present results agree with other studies developed in forested areas regarding the predominance of species with functional traits with some dependence on forest resources, such as mixed and understory foraging stratum and intermediate forest-dependence (e.g., riparian, Domínguez-López and Ortega-Álvarez 2014;Batisteli et al 2018;Maure et al 2018). The urban greenspaces studied here are forested (Online Resource 1a), which favors forestdwelling species that require specific resources in these urban landscapes.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies have found an influence of habitat in functional metrics of forest bird assemblages. However, these studies have evaluated strong gradients of disturbance or environmental changes, for example, the effects of monoculture on Amazonian birds (Almeida et al 2016) and the reduction of riparian forest width on birds of the Atlantic Forest (Maure et al 2018). We suggest that environmental differences among our plots were not strong enough to generate major changes in functional structure of the assemblages.…”
Section: Discussionmentioning
confidence: 89%
“…Differences in dietary guild composition observed across the different disturbance categories in forests, provide initial indications that omnivores may cope well under disturbance pressures. Vulnerability of some dietary guilds may explain the varying functional group compositions observed in human-altered forest sites (Luke et al 2014;Maure et al 2018). Given that most species in our study were omnivores and there was only one insectivore (large-headed shrew) and one herbivore species (typical striped grass mouse), no general statement about these two more specialized dietary guilds can be made.…”
Section: Discussionmentioning
confidence: 91%